Transphobia as trauma and curatorial criterion of cisnormativity (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article focuses on the phenomenon of transphobia to analyze the behavior of cisnormativity as a hegemonic paradigm of socio-cultural organization. In dialogue with thinkers of the cuír theory, it is argued that transphobia is not a mechanism of oppression that occurs through the demonstration of force, but rather a traumatic response of cisnormativity when envisioning its own end. A reflection is also made on the cisgender dominance of spaces of power in the theater scene, such as production, curation and criticism, in order to identify a supposedly progressive discourse of “inclusion” as a sophisticated version of the functioning of transphobia as trauma.
Keywords: transgenderity; transphobia; cisnormativity; cuír theory; curation